Seleksi Rumah Tidak Layak Huni Dengan Sistem Pendukung Keputusan Menggunakan Metode SAW Dan Weight Product - Eka Ridhawati; Didi Susianto; Yuri Fitrian (SAINS DAN INFORMATIKA : RESEARCH OF SCIENCE AND INFORMATIC, 2022)
In rural areas there are still a lot of houses that are not suitable for habitation and this is caused by several factors such as below-average income which affects the standard of living of the community. This condition affects the number of residents' houses which are still in uninhabitable conditions and urgently need to be dissected through house surgery assistance. SAW and WP methods can help in making decisions, but calculations using the SAW and WP methods only produce the largest value which will be selected as the best alternative. From the results of testing the system developed using the Simple Additive Weighting ( SAW ) and weighted product (WP) methods. The design of decision making for house renovation assistance recipients at the Department of Housing and Settlement Areas is based on criteria, namely income, housing conditions, asset ownership, family dependents, and location using the SAW and WP methods. From the calculation of the alternative values, the final result of the calculation and implementation of the SAW and WP methods who are entitled to receive renovations to uninhabitable houses is Darmono.